PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, PROFITABILITAS, LEVERAGE, DAN PERTUMBUHAN PENJUALAN TERHADAP TAX AVOIDANCE - Rosa Dewinta, Ida Ayu; Ery Setiawan, Putu (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
This study aimed to examine the effect of firm size, firm age, profitability, leverage and sales growth against tax avoidance. This study focused on manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period 2011-2014. 176 number of observations sample obtained by the method nonprobability sampling purposive sampling technique. The analysis technique used in this research is multiple linear regression analysis. The analysis showed that the size of the company, firm age, profitability, sales growth has positive effect on tax avoidance. This means that the higher the company's size, age of the company, profitability and sales growth will result in increased tax avoidance. Leverage has no effect on tax avoidance. This means that the higher leverage will not affect the increase in tax avoidance.
Keywords: tax avoidance, firm size, firm age, profitability, leverage, and sales growth